QUANTITATIVE ANALYTICAL RESULTS ON TOPOGRAPHIC FEATURE OF THE VIETNAM’S CONTINENTAL SHELF WITHIN COORDINATES 11.7 - 14.00 AND 109.5 - 110.20 - Thanh, Phi Truong (Vietnam Journal of Marine Science and Technology, 2016)
This paper presents some analytical results of bathymetry data according to three maps: Three dimensions (3D), slope, aspect on the continental slope and shelf area in the central part of Vietnam within the coordinates of 11.7 - 14.00 and 109.5 - 110.20. The obtained results have reflected clearly the geomorphic characteristics in this area. For example, on the 3D map, the continental slope exists three steps at the depths of 500 - 700 m, 1,250 m, and 1,500 - 1,700 m, running along the meridian 109.70, about 250 km long. These results are also shown on the slope and aspect map. On the slope map, from the depth of about 250 m to the first step base, the slope angle varies within 5 - 200 and from the first step base to second step base, the slope angle varies within 5 - 100; In the remaining part, the slope angle varies within 2 - 80. The other analytical results from the aspect map are also shown clearly, the aspect direction on the wall of three slope steps varies from 50 to 1000, reflecting the topographic slope towards the east, where is abyssal plain. The existence of Pliocene - Quaternary sediments along with steep continental slope caused landslide phenomenon in this area.